Synthesis and Characterisation of Silver Nanoparticles Using Vernonia Cinerea Aqueous Extract and Their Cytotoxicity Activity against Kasumi-1 Cell Line - Mohamad Zani, Radhiyatul Akma; Ahmad, Nor Hazwani; Abdul Razak, Siti Razila (Universiti Teknologi Malaysia, 2016)
Green synthesis is preferable for the synthesis of silver nanoparticles (AgNPs) due to its rapid and reliable process. Previous studies have demonstrated that active compounds present in Vernonia cinerea (V. cinerea) are responsible for bioreduction during synthesis of AgNPs. Hence, in this present study, aqueous extract of V. cinerea was used to synthesise AgNPs. The V. cinerea aqueous extract was added to AgNO3 solution (25 mL, 50 mL and 100 mL) to produce mixture with ratio of 1:5, 1:10 and 1:20. The formation of V. cinerea-AgNPs was monitored for colour changes, and characterised by UV-Vis spectroscopy, transmission electron microscopy (TEM) and zeta potential analyses. The UV-Vis spectrum of V. cinerea-AgNPs showed absorption maxima at 450 nm while TEM images showed that the V. cinerea-AgNPs were spherical in shape with an average size of 15.29 nm. The zeta value of synthesised V. cinerea-AgNPs was – 29.50 mV with a peak area of 100 % intensity. The cytotoxicity of V. cinerea-AgNPs were tested in vitro on Kasumi-1 cells using MTS assay. The MTS assay revealed that the V. cinerea-AgNPs with the concentration of 31.25 g/mL at 72 hr produced highest cytotoxicity effects on Kasumi-1 cells. These results indicate that AgNPs can be biologically synthesised from V. cinerea and has potential to be used as an anticancer agents on acute myeloid leukaemia cell line